The Interrelation between Емigration, Human Capital Reproduction and Gender Risks in the Republic of Armenia - Astvatsaturov, Sedrak; Marzpanyan, Harutyun (Journal of Sociology: Bulletin of Yerevan University, 2014)
The article addresses the yet-to-be-studied issue within the social research; i.e. the issue of interrelated study of gender risks, migration processes and human capital reproduction in conditions of social transformations in RA. Based on the “comprehensively precise” approach of study of gender risks developed by the authors and given the importance of adjustment of human capital theory related to Armenia (where the labour emigration bears not an individual but a mass character), the mentioned interrelations are considered to be based on the interacting macro, meso and micro levels of scientific analysis. The contradictions between the individual and social utility of migration are identified. The authors argue that as the gender imbalance, segregation and discrimination are the manifestations of negative risks, then a thorough sociological analysis of specific problems in the areas of employment and labour market of Armenia (including the groups of the unemployed) has been carried out. The latter, together with other factors, contributes to increasing the migration risks and hindering the application, accumulation and reproduction of both the individual and, first of all, total human capital within the country. In this regard, the authors, emphasize the importance of establishment of institutional structures of gender policy (in the narrow meaning of the word), as well as the necessity of elaborating scientific criteria, clear-cut indicators and gender statistics, which would have reflected the real interrelation between macro-processes, accumulation of human capital and managing gender and migration risks.
Keywords: emigration, migration risks, migration risks management, human capital, human capital theory, human capital reproduction, gender risks, gender policy